Adaptive Strategies for Coastal Resource Management in the Era of Climate Change: Literature Review - Ardiyanti Ardiyanti; Fahrul Kahfi; Rusli Rusli (Pemuda Peduli Publikasi Insan Ilmiah, 2025)
Purpose: This study examines adaptive strategies in coastal resource management within the context of climate change, with emphasis on governance integration, community participation, ecosystem resilience, and technological adaptation. Subjects and Methods: The research employed a systematic literature review (SLR) using the PRISMA framework to ensure transparency and methodological rigor. Data were collected from Scopus, Web of Science, ScienceDirect, JSTOR, and Google Scholar covering publications from 2000–2025. From 137 identified records, 84 studies were selected through screening and eligibility assessment. The selected studies were analyzed using inductive thematic analysis and coding matrices. Results: The findings reveal four dominant adaptation dimensions: institutional and policy-based adaptation, community-based adaptation, ecosystem-based adaptation, and technological adaptation. Policy integration and decentralization were widely emphasized, although institutional rigidity and fragmented governance remained significant barriers. Participatory governance and indigenous knowledge contributed to local resilience but were often constrained by unequal participation and marginalization. Ecosystem-based approaches such as mangrove restoration demonstrated strong ecological and social benefits, while technology-driven adaptation improved preparedness despite concerns regarding financial inequality and limited inclusiveness. Conclusions: Effective coastal climate adaptation requires adaptive governance frameworks integrating institutional flexibility, ecological sustainability, technological innovation, and inclusive community participation to strengthen long-term resilience under increasing climate uncertainty.